CHAROITE. EXPERIMENTAL STUDIES - M. V. Marchuk; V. Ya. Medvedev; L. A. Ivanova; T. S. Sokolova; B. S. Danilov; D. P. Gladkochub (Геодинамика и тектонофизика, 2016)
The article provides an overview of experimental studies of charoite and charoite-containing rock formation hypotheses. The authors conducted experiments to clarify charoite and host rocks interaction and study charoite transformation processes at high temperatures. A series of experiments was aimed at improving the substandard charoite samples. The experiments show the formation of polymineral reaction zones due to the contact interaction between charoite and microcline-arfvedsonite lamprophyre. By studying the newly formed phases, the authors reveal the distribution of elements by phases and establish their compositions. It is shown that thermal decomposition of charoite leads to the formation of wollastonite, which amount increases with the temperature increase from 800 to 1000 °C, and heating above 1200 °C leads to the formation of pseudowollastonite. The physicochemical simulation of charoite decomposition under the specified temperatures and pressure shows the following paragenesis: quartz, wollastonite, alkaline pyroxene (aegerine), microcline, rhodonite, and sphene.The experiments prove the formation of charoite at low temperatures and the lack of silicate melt in the systems studied. The calculated values are consistent with the results of experiments conducted to study the charoite and host rocks interaction, which allows identifying phases potentially co-existing with wollastonite.Special studies using by the coloring technique were conducted to improve the decorative properties of charoite. The color close to natural high-grade charoite coloration was achieved by keeping the rock samples in the active bright purple dye 4KT solution for 72 hours at a temperature of 70 to 90 °C.